Deciphering the Semiotic Landscape of Love in Lana Del Rey's 'Mariners Apartment Complex' Song Lyrics - Andres, Salva de Shauma (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2024)
This research paper presents an analysis of Lana Del Rey's song